2020
DOI: 10.1101/2020.09.16.299701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteome-wide Profiling of RNA-Binding Protein Responses to flg22 Reveals Novel Components of Plant Immunity

Abstract: RNA-binding proteins (RBPs) play critical roles in post-transcriptional gene regulation and are known to contribute to plant immunity. To understand the responses of cellular RBPs to an immune elicitor, we applied RNA interactome capture to Arabidopsis leaves treated with flg22. Strikingly, flg22 induced a pervasive remodelling of the cellular RBPome affecting 186 proteins. Flg22-responsive RBPs included classical RBPs involved in RNA metabolism as well as non-canonical RBPs. RBP responders detected after 2h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, Spm and less markedly Put dampened the flg22-elicited expression of ribosome biogenesis genes ( Supplementary Figs S13, S18 ). Bach-Pages et al (2020 , Preprint) found that the RNA-binding activity of eukaryotic initiation factors, elongation factors, and ribosomal proteins was inhibited in response to flg22. The overexpression of genes encoding ribosomal proteins caused by flg22 might be a compensatory mechanism to the PAMP-triggered inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Spm and less markedly Put dampened the flg22-elicited expression of ribosome biogenesis genes ( Supplementary Figs S13, S18 ). Bach-Pages et al (2020 , Preprint) found that the RNA-binding activity of eukaryotic initiation factors, elongation factors, and ribosomal proteins was inhibited in response to flg22. The overexpression of genes encoding ribosomal proteins caused by flg22 might be a compensatory mechanism to the PAMP-triggered inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this suggests that CBE1, PAT1, and eIF4E regulate RBOHD levels, either post-transcriptionally or co/post-translationally, and thereby affect elicitor-induced ROS production. Translational regulation of plant immunity has recently been proposed, as elicitor perception induces global translational reprogramming 3436 and remodeling of the cellular RNA-binding proteome 37 . Notably, some of these RNA-binding proteins (RBPs) control transcripts encoding important immune signaling components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the decapping and deadenylation protein complex as well as NMD factors have been shown to regulate stress-responsive transcripts 4651 . Accordingly, these changes at the level of RBPs and transcripts contribute to plant immune responses against viruses (which depend on host translation) and other pathogens 37,50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RBOHD activity has been shown to antagonize SA-induced pro-cell death signals in Arabidopsis (Torres et al, 2005), thus revealing a complex interrelationship between ROS and defense outputs. (Bach-Pages et al, 2020) found that the RNA-binding activity of eurkaryotic initiation factors, elongation factors and ribosomal proteins was inhibited in response to flg22. The upregulation in gene expression of ribosomal proteins caused by flg22 might be a compensatory mechanism to the PAMP-triggered inhibition of translation.…”
Section: Discussionmentioning
confidence: 99%